Analysis of Conduction and Charging Mechanisms in Atomic Layer Deposited Multilayered HfO2/Al2O3 Stacks for Use in Charge Trapping Flash Memories - Nenad Novkovski; Albena Paskaleva; Aleksandar Skeparovski; Dencho Spassov (Advances in Condensed Matter Physics)
Method for characterization of electrical and trapping properties of multilayered high permittivity stacks for use in charge trapping flash memories is proposed. Application of the method to the case of multilayered HfO2/Al2O3 stacks is presented. By applying our previously developed comprehensive model for MOS structures containing high-κ dielectrics on the J-V characteristics measured in the voltage range without marked degradation and charge trapping (from −3 V to +3 V), several parameters of the structure connected to the interfacial layer and the conduction mechanisms have been extracted. We found that the above analysis gives precise information on the main characteristics and the quality of the injection layer. C-V characteristics of stressed (with write and erase pulses) structures recorded in a limited range of voltages between −1 V and +1 V (where neither significant charge trapping nor visible degradation of the structures is expected to occur) were used in order to provide measures of the effect of stresses with no influence of the measurement process. Both trapped charge and the distribution of interface states have been determined using modified Terman method for fresh structures and for structures stressed with write and erase cycles. The proposed method allows determination of charge trapping and interface state with high resolution, promising a precise characterization of multilayered high permittivity stacks for use in charge trapping flash memories.